Spare Parts Inventory Planning In The Aircraft MRO Industry By Integrating Demand Categorization And The RPA (s,S) Policy Method - Raga C. A. Pambudi; Yuri M. Zagloel (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Air transportation in Indonesia has experienced significant growth in passenger traffic over the past few years, driven by factors such as travel distance, time efficiency, safety, and service quality. From a safety perspective, one critical aspect that must not be overlooked is the availability of spare parts during Maintenance, Repair, and Overhaul (MRO) activities, as it directly affects aircraft airworthiness and flight safety. Demand for spare parts in the MRO industry is influenced by maintenance schedules and aircraft utilization, resulting in varying demand patterns characterized by different levels of demand variability and demand frequency. This study focuses on inventory planning in an Indonesian aircraft MRO company using the Revised Power Approximation (RPA) (s,S) policy. The proposed inventory policy is evaluated by comparing its performance with the company's existing inventory management approach in terms of total inventory cost and customer service level. The results demonstrate that the RPA (s,S) policy can effectively reduce inventory-related costs and improve service performance, thereby enhancing spare parts availability to support maintenance operations and flight safety.